2022
DOI: 10.3390/ijerph192416560
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk for Vulnerable Infants: Breastfeeding and Milk Sharing Practice among Ghanaian Women

Abstract: Human milk has the best impact on childhood survival. In Ghana, it is estimated that 43% of women exclusively breastfeed for 0–5 months and only 42% of breastfeeding mothers continue through 20–23 months. Although the Ghanaian government has implemented policies to facilitate exclusive breastfeeding, substantial gaps to achieve optimal newborn health and wellbeing remain. The purpose of this study was to evaluate breastfeeding prevalence and human milk sharing practices among Ghanaian women. Qualitative respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Many investigators have reported that PH is the most common cause of breastfeeding failure 5–7. Breast milk has been identified as the gold standard to provide nutritional support for all infants and prevent infant morbidity and mortality 8–10. For mothers, breast feeding can decrease the risk of breast cancer, ovarian cancer and type 2 diabetes 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigators have reported that PH is the most common cause of breastfeeding failure 5–7. Breast milk has been identified as the gold standard to provide nutritional support for all infants and prevent infant morbidity and mortality 8–10. For mothers, breast feeding can decrease the risk of breast cancer, ovarian cancer and type 2 diabetes 11.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Breast milk has been identified as the gold standard to provide nutritional support for all infants and prevent infant morbidity and mortality. [8][9][10] For mothers, breast feeding can decrease the risk of breast cancer, ovarian cancer and type 2 diabetes. 11 Thus, if a mother's own milk is insufficient, it poses challenges not only to mothers who desire to provide milk for their babies, but also to infants who need optimal nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the Ghanaian government has put rules in place to encourage exclusive breastfeeding, there are still significant obstacles standing in the way of achieving the best possible outcomes for newborn health and wellbeing, necessitating the possibility of breast milk banking. In a previous study, 8% of mothers admitted to ever giving breastmilk to another mother without having the milk screened [13]. As a result, it's critical to investigate the WHO suggestion of donor banking for breastmilk, which offers the chance for the milk to be checked before use.…”
Section: Introductionmentioning
confidence: 99%
“…In light of these challenges, some women and families turn to milk sharing or wet-nursing to fulfill the need for breastmilk. A recent study examining milk sharing practices among Ghanaian women reports that 8% of the sample ( n = 1050) indicated that they had ever shared milk with another lactating mother ( 21 ).…”
Section: Introductionmentioning
confidence: 99%